Characterising the fruit and vegetables consumer ethnocentrism in a southern european country: an assesment of the reliability and validity of the CETSCALE in Portugal - Miguel, L.; Marques, S.; Duarte, A. P. (Food Quality and Preference, 2023)
This paper aims to characterize the consumer ethnocentrism (CE) and its implications on food products evaluation in a Southern European Country-Portugal. The 10-item version of the Consumer Ethnocentric Tendencies Scale (CETSCALE) was used. It’s validity and dimensionality were assessed together with the ethnocentric characteristics among fruit and vegetables consumers. A questionnaire was conducted through Computer Assisted Phone Interviews – (CATI) to the person responsible for the household food purchase in the two largest Portuguese metropolitan areas Lisbon and Oporto resulting in 700 valid responses. The food products under consideration were fruit and vegetables as they represent the largest sales in the major retail chains and also are considered low value products. Moreover, Portuguese consumption of fruit and vegetables is the highest considering the European consumption. The validity and the reliability of the CETSCALE have been confirmed as the showing a high degree reliability. The multidimensionality of the construct has also been validated with two factors obtained and named soft and hight ethnocentrism. As far as authors are aware, this is the first study conducted in Portugal and considering two specific food categories – fruit and vegetables. The present study contributes to the ongoing debate on origin labelling in a time of increasing globalisation markets.